The ability of Lactobacillus helveticus -13 (Lh-13) Isolate Isolated from Lactic Acid Products to form A biofilm by Applying Modern Microscopy Methods - Amirkhanova, Zh.; Akhmetova, S.; Kozhakhmetov, S.; Kushugulova, A.; Bodeeva, R.; Ahvlediani, L.; Turmukhambetova, A. (Jordan Journal of Biological Sciences, 2023)
This article presents the study of the morpho-cultural properties and biofilm formation of lactobacilli isolated from lactic acid products (irimchik, suzbe, cheese, ashygan kozhe) produced in different districts of the Karaganda region. The species of the isolated lactic acid bacillus isolates were identified by using a MALDI-TOF mass spectrometer. The evaluation of the resistance of the isolates to various stress factors, such as the ability to survive at low acidic pH values and in the presence of bile, made it possible to identify some promising isolates – Lactobacillus helveticus -13 (Lh-13) and Lactiplantibacillus plantarum – 5 (Lpl-5), for studying antimicrobial and biofilm-forming activity. The antimicrobial activity of Lh-13, Lpl-5 was closely studied. They have a certain level of antibacterial and fungicidal activities, which indicates their pronounced inhibition against indicator microorganisms. Using a laboratory robot, TecanEVolizer100 (Tecan), the optical density of Lh-13, Lpl-5 was studied in the wells of polystyrene plates, reflecting the intensity of biofilm formation along their surface. Using laser capture microdissection, the images of cell morphology in biofilm of Lh-13 isolates included in the matrix were obtained. The atomic force microscopy made it possible to study the two and three-dimensional morphological images of biofilm-forming isolates of Lh-13.
Keywords: lactobacilli; mass spectrometry (MALDI-TOF MS); biofilm; laser capture microdissection; atomic force microscopy; antimicrobial activity